2018
DOI: 10.1016/j.athoracsur.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sutureless Repair of Total Anomalous Pulmonary Venous Connection: Suture-and-Open Technique

Abstract: We used a suture-and-open technique with a biatrial incision for primary sutureless repair of total anomalous pulmonary venous connection (TAPVC). With this technique, the common pulmonary venous sinus and its branching pulmonary veins are opened after completion of suturing of the left atrial incision to the pericardium around the common pulmonary venous sinus and its branching veins. The technique allows the primary sutureless repair of TAPVC to be done in a less bloody field under full-flow cardiopulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the study period, 49 patients underwent primary TAPVD repair. The anatomical type distribution was supracardiac in 51% (25), cardiac in 18% (9), infracardiac in 16% (8), and mixed in 14% (7) of the patients. Single ventricle lesions and heterotaxy syndromes were each present in 12% (6) of the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study period, 49 patients underwent primary TAPVD repair. The anatomical type distribution was supracardiac in 51% (25), cardiac in 18% (9), infracardiac in 16% (8), and mixed in 14% (7) of the patients. Single ventricle lesions and heterotaxy syndromes were each present in 12% (6) of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…The operative mortality of surgery varies widely in the literature between 4 and 35% [1][2][3][4]. Anatomical type [5], stenosis of the drainage pathway [6], surgical technique [6][7][8][9][10][11][12], and time era all are reported to have an important effect of short-and long-term outcomes. Associated single ventricle anomalies carry a particularly poor prognosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…infracardiac TAPVC). However, in this case, the CPV was located lower right than usual, therefore, we performed transverse incision, 5 which enabled sutureless repair using both left and right atrial walls.…”
Section: Discussionmentioning
confidence: 97%
“…5,6,9 At present, more and more studies suggest that for TAPVC patients who may be complicated by PVO after surgery, the initial orthopedic surgery may achieve better results by using the sutureless technique. [10][11][12] Sutureless surgery has obvious advantages as a primary correction of TAPVC: (1) this surgery can be applied to any type of TAPVC, and it is especially suitable for children with preoperative PVO 13 ; (2) The surgical field of pulmonary vein branches is better, thereby reducing the application of deep hypothermic circulatory arrest 14 ; (3) Avoiding direct anastomosis of the pulmonary vein endothelium, reducing local scarring and PVO caused by anastomotic distortion. 15 Conventional sutureless technology also has some drawbacks.…”
Section: Sutureless Proceduresmentioning
confidence: 99%
“…Wen et al 40 showed that preoperative pulmonary vein obstruction is a risk factor for postoperative pulmonary vein obstruction, which may be because it is difficult to form a large anastomosis between the small pulmonary vein and the left atrium, leading to the progression of postoperative pulmonary vein obstruction. In traditional surgical repair, pulmonary vein convergence and its branches are directly anastomosed with the left atrium, which may distort the pulmonary vein and damage the endothelial cells of pulmonary vein convergence, 10 resulting in a high incidence of postoperative PVO. Sutureless technology minimizes the contortion of pulmonary venous convergence and its branching veins to minimize the effect of flow turbulence.…”
Section: Risk Factors For Pvo and Death After Tapvcmentioning
confidence: 99%